Understanding solid-state electronics - Don L. Cannon; Shack, Radio (Carnel Howard W. Sams & Co., 1991)
For anyone who wants to understand how semiconductor devices work, either alone or in systems. Covers basic theory and use of diodes and transistors; bipolar, MOS, and linear integrated circuits. Clear down to earth language, ideal for self -study.